Highly efficient, high speed vertical photodiodes based on few-layer MoS2. (26th October 2016) - Li, Zhen; Chen, Jihan; Dhall, Rohan; Cronin, Stephen B
Abstract: Layered transition metal dichalcogenides, such as MoS2, have recently emerged as a promising material system for electronic and optoelectronic applications. The two-dimensional nature of these materials enables facile integration for vertical device design with novel properties. Here, we report highly efficient photocurrent generation from vertical MoS2 devices fabricated using asymmetric metal contacts, exhibiting an external quantum efficiency of up to 7%. Compared to in-plane MoS2 devices, the vertical design of these devices has a much larger junction area, which is essential for achieving highly efficient photovoltaic devices. Photocurrent and photovoltage spectra are measured over the photon energy range from 1.25 to 2.5 eV, covering both the 1.8 eV direct K-point optical transition and the 1.3 eV Σ-point indirect transition in MoS2 . Photocurrent peaks corresponding to both direct and indirect transitions are observed in the photocurrent spectra and exhibit different photovoltage–current characteristics. Compared to previous in-plane devices, a substantially shorter photoresponse time of 7.3 μ s is achieved due to fast carrier sweeping in the vertical devices, which exhibit a −3 dB cutoff frequency of 48 kHz.